Local peritoneal toxicity from adjuvant pressurized intraperitoneal aerosol chemotherapy with oxaliplatin in high-risk patients with colonic cancer. Issue 5 (18th February 2021) - Graversen, M; Detlefsen, S; Pfeiffer, P; B Mortensen, M
Abstract : This research letter describes unexpected and unacceptable local toxicity manifesting as abdominal pain after adjuvant pressurized intraperitoneal aerosol chemotherapy with 92 mg/m 2 oxaliplatin in the PIPAC-OPC3 study. It is not clear whether the toxicity is dose- or drug-dependent (or both), but the preliminary data suggest that tolerability is improved by dose reduction to 46 mg/m 2 .